First-episode bipolar disorder is associated with erythrocyte membrane docosahexaenoic acid deficits: Dissociation from clinical response to lithium or quetiapine. Issue 2 (15th December 2015) - McNamara, Robert K.; Jandacek, Ronald; Tso, Patrick; Blom, Thomas J.; Welge, Jeffrey A.; Strawn, Jeffrey R.; Adler, Caleb M.; DelBello, Melissa P.; Strakowski, Stephen M.
Abstract: Deficits in long-chain omega-3 (LC n −3) fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) may be associated with the pathophysiology of bipolar disorder. However, LC n −3 fatty acid status at the initial onset of mania and its association with treatment response are not known. Erythrocyte membrane fatty acid composition was determined in first-episode bipolar manic or mixed ( n =40) and healthy ( n =40) subjects. Mood symptom ratings were obtained with the Young Mania Rating Scale (YMRS) and the Hamilton Depression Rating Scale (HDRS). Erythrocyte fatty acid composition and clinical ratings were also determined within a sub-group of bipolar subjects following 8-week ( n =19) or 52-week ( n =11) open-label treatment with lithium or quetiapine. At baseline bipolar subjects exhibited significantly lower erythrocyte docosahexaenoic acid (DHA, 22:6 n −3) composition compared with healthy subjects (−23%, p <0.0001). EPA (20:5 n −3) and docosapentanoic acid (22:5 n −3), and LC n −6 fatty acids including arachidonic acid were not different. Following 8- or 52-week treatment with lithium or quetiapine, YMRS and HDRS total scores decreased significantly whereas erythrocyte fatty acids including DHA did not change. These data indicate that selective erythrocyte DHA deficits coincide with the initial onset of manic symptoms, and reductions in mood symptoms following treatment are not mediated by changes in fatty acid status. Highlights: Long-chain omega-3 fatty acid status at the initial onset of mania is not known. Bipolar subjects exhibited significantly lower DHA levels compared with healthy subjects Lithium or quetiapine decreased manic and depressive symptoms but did not alter DHA levels DHA deficits coincide with the initial onset of mania but are not associated with treatment response